Avaliação dos produtos de emissão a partir da pirólise de assentos automotivos feitos de fibra de coco e de espuma de poliuretano - Salazar, Vera Lúcia Pimentel [UNESP]; Caraschi, José Cláudio [UNESP]; Leão, Alcides Lopes [UNESP] (Associação Brasileira de Engenharia Sanitária e Ambiental - ABES, 2005)
The objective of this work is to compare automobile seats made of coconut fiber mats with latex (MFCL) versus polyurethane foam (EPU), evaluating the possibility of the first replace the second due to the fact of the renewability and biodegradability of the natural fiber. These materials were submitted to analysis of the pyrolysis by-products was made, using the gas chromatography coupled with mass spectrometer. Also, it was made thermogravimetric analysis. It was observed that at 800ºC the materials presented a higher number of toxic vapors, and it was noticed that all components that were present in this pyrolysis of coir fiber and of MFCL were also found in the EPU, and even other components as hydrogen cyanate and nitrile compound were found in EPU pyrolysis. Therefore, it can be stated that pyrolysis by-products at 800ºC of EPU are much more hazardous than those produced by the natural materials at the same conditions. Regarding the thermal analysis, it was observed that above 270ºC begins the thermal decomposition of all the studied materials.

O presente trabalho visa comparar assentos automobilísticos feitos de manta de fibra de coco com látex (MFCL) em relação à espuma de poliuretano (EPU), avaliando a possibilidade do primeiro substituir o segundo, devido ao fato da fibra natural ser biodegradável e renovável. Esses materiais foram submetidos à análise termogravimétrica (TGA), pirólise e análise dos produtos de pirólise por cromatografia gasosa acoplada ao espectrômetro de massa. Verificou-se que a pirólise a 800ºC apresentou grande número de gases tóxicos, e comparando os materiais observou-se que a EPU emitiu gases mais tóxicos na combustão que aqueles produzidos pelos outros materiais sob as mesmas condições, tais como o cianeto de hidrogênio e compostos de nitrila. Quanto às análises de TGA, verificou-se que acima de 270ºC inicia-se a degradação térmica de todos materiais.
Evaluation of emission products from pyrolysis of car seats made of coir fiber and of polyurethane foam
Keywords: Pyrolysis; TGA; polyurethane foam; coconut fiber; latex; automobile seats; Pirólise; TGA; espuma de poliuretano; fibra de coco; manta de fibra de coco com látex; assentos automobilísticos